Satisfaction of Malaysian Muslim tourists with halal facilities in Japan - Wan Sulong, Wan Muhammad; Mohd Zin, Zaid; Husain, Salina; Othman, Mohd Sukki; Ismail, Muhd Zulkifli (Human Resource Management Academic Research Society, 2021)
Due to the rapid growth of the Muslim population, Halal or Islamic tourism is a market segment that is constantly increasing not only in Muslim countries but also globally. Japan is one of the forefront countries that are becoming more welcoming to Muslim customers. A combination of halal-friendly products and services, as well as omotenashi (traditional Japanese hospitality), is attracting visitors from Muslim countries, including Malaysia. The purpose of this study is to determine the level of satisfaction of Malaysian Muslim tourists with halal facilities based on their visit to Japan. Surveys and questionnaires were utilised to collect data from a total of 288 respondents. Respondents are particularly concerned about the availability of halal facilities to meet religious needs, according to the study's findings. They like the cleanliness of the prayer space at the airport, as well as the amenities gave, such as ablution areas, prayer direction (Qibla), and a prayer rug. They were extremely pleased with the mosque's cleanliness and facilities. On the other hand, they are dissatisfied with the prayer facilities available at tourist destinations because only a small percentage of them provide a prayer room for Muslims. The practice of prayer in public places, on the other hand, is not interrupted or restricted. In regard to accommodations, they believe it is clean and suited for prayer. However, because there is no Qibla direction in the room, no prayer facilities, no halal cuisine, and no prayer time information supplied at the counter, the majority of the accommodations are not very accommodating to Muslim demands.